SPORT GAME - FOOTBALL DURING THE UNIVERSITY PHYSICAL EDUCATION LESSON - Finichiu Marin (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
The determination of the most significant operational models for the technical - tactical training in the sport game - football, are designed to increase the efficiency of the used methods and means. The well-known sport game - football is capable to mobilize all forces, to keep up the interest, to reach a maximum efficiency and to highlight another feature of games - their attractiveness and spontaneity.